Eishockeyverletzungen über 10 Jahre im Deutschen Eishockeyverband - eine prospektive 10-Jahres-Studie von 523 internationalen Spielen - Gröger, A. (Sportverletzung Sportschaden, 2001)
Since January 1986 all injuries in players of the German national hockey teams (juniors A/B and seniors A/B), which have occurred during international competitions, have been registrated and evaluated by using a strict definition of injury, standardized reporting strategies and diagnosis by the team physician. Patterns of injury have been identified and correlations between position, zone and cause of injury could be analysed and, as a consequence, measures were taken to prevent them. A total of 147 injuries forcing a consecutive absence from the game during 523 international games of the German national teams were reported. During the 10 year period there was a marked decrease of the total number and incidence of injuries. In addition, injury rate and average absence from game time improved. There were more frequent concussions of the brain but the total number of facial injuries dropped after the introduction of a visor and the full face mask especially in junior hockey. The forward was the position most at risk to be injured and most injuries were caused by players contact.